HEAVY METAL POLLUTANT SORPTION IN AQUATIC ENVIRONMENT BY MICROALGAE CONSORTIUM - Astri Rinanti; Melati Ferianita Fachrul; Rositayanti Hadisoebroto; Sinthya Desty; Rahmadhania Rahmadhania; Della Annisa Widyaningrum; Noor Aida Saad (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Industrial waste that contains heavy metal can cause environmental problem because of its toxicity, persistency and accumulation level in the environment. Biosorption process is highly influenced by temperature, pH, light, contact time, and ratio of surface area. Microalgae which possess two functional groups that are able to react on metal ion in a solution can be exploited to overcome environmental pollution due to heavy metal compound. Closed cultivation system in a photobioreactor is utilized to overcome contamination and evaporation problems on open pond system. Heavy metal analysis is conducted by utilizing Atomic Absorption Spectroscopy (AAS), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscope (SEM). This article provides information on biosorption as alternative technology to overcome heavy metal in water areas with no side effects on the environment with advantages of the absence of secondary pollutants, high level of efficiency, and relatively economic compared to physic-chemical method heavy metal removal methods